Influence of maternal and infant variables on school age children within the Project Obesity Zero - Jardim, Carla (2012)
Introduction: Obesity is considered by World Health Organization as a serious public health concern. The maternal and infant variables are essential to a successful intervention on the prevention of childhood obesity. Objective: Evaluate the influence of maternal and infant variables on nutritional status of children in a community-based intervention program known as Project Obesity Zero (POZ). Methods: POZ is a quasi-experimental, multicentric study developed in 2009 in five municipalities of Portugal (Beja, Cascais, Mealhada, Melgaço and Silves) articulated with Healthcare Centres and local governments. The program offered, to children and their families, a four stages intervention: 1) Sessions of Individual Nutrition Counselling, 2) Healthy Cooking Workshop, 3) Children’s Group Sessions and 4) Parents/families Group Counselling. The criteria used to define nutritional status of children were the CDC Growth charts (2000). This criteria was adopted by the Portuguese Ministry of Health. The information about maternal-infant variables was collected from the Questionnaire about food habits, food behaviours and nutrition knowledge directed to parents. Descriptive analyses were evaluated. Differences between groups were tested using chi-square test. Crude odds ratio (OR) with 95% CI were calculated by univariate analysis and adjusted OR were calculated by multivariate logistic regression analysis. A P-value<0,05 level was considered statistically significant. Results: From the 293 children evaluated, 52% were female and 48% were male; 9,2% had normal weight, 37,9% were overweight and 52,9% were obese. 80,4% of the children decreased their BMI percentile and Mealhada was the municipality with the greater reduction (92,0%) (p<0,01). The greater reduction of BMI percentile was found in children who were breastfed (81,6%), in children who began the food diversification between 4 and 6 months of age (84,6%) and children that have introduced soup in first place in food diversification (90,6%) (p <0.05). Conclusion: This study adds evidence to the eficacy of community-based projects on the prevention of childhood obesity, enphatizing the importance of the matenal-infant variables in these interventions.